2016
DOI: 10.3390/ijms17081305
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Aciniform Silk Repetitive Domain Backbone Dynamics and Hydrodynamic Modularity

Abstract: Spider aciniform (wrapping) silk is a remarkable fibrillar biomaterial with outstanding mechanical properties. It is a modular protein consisting, in Argiope trifasciata, of a core repetitive domain of 200 amino acid units (W units). In solution, the W units comprise a globular folded core, with five α-helices, and disordered tails that are linked to form a ~63-residue intrinsically disordered linker in concatemers. Herein, we present nuclear magnetic resonance (NMR) spectroscopy-based 15N spin relaxation anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 64 publications
2
11
0
Order By: Relevance
“…Prominent negative bands at 208 and 220 nm, along with strongly positive ellipticity at 195 nm, indicate that all proteins contain significant α-helical content in solution. This is consistent with our solution-state NMR structures of W 1 and W 2 , showing each W unit to contain a globular domains of 5 α-helices connected to its neighbor by an intrinsically disordered linker. ,, All CTD structures reported to date also, coincidentally, contain 5 helices followed by a disordered segment. ,,, CD spectra representative of a convolution of helical and disordered structures is therefore fully expected, but the exceptional degree of similarity of mean residue ellipticity for all four protein constructs is striking and would not be predicted a priori. As a whole, it is clear that swapping of a W unit for a CTD does not perturb the structuring or independence of the repetitive units in solution and also that CTDs and W unit have a similar overall structural composition.…”
Section: Results and Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Prominent negative bands at 208 and 220 nm, along with strongly positive ellipticity at 195 nm, indicate that all proteins contain significant α-helical content in solution. This is consistent with our solution-state NMR structures of W 1 and W 2 , showing each W unit to contain a globular domains of 5 α-helices connected to its neighbor by an intrinsically disordered linker. ,, All CTD structures reported to date also, coincidentally, contain 5 helices followed by a disordered segment. ,,, CD spectra representative of a convolution of helical and disordered structures is therefore fully expected, but the exceptional degree of similarity of mean residue ellipticity for all four protein constructs is striking and would not be predicted a priori. As a whole, it is clear that swapping of a W unit for a CTD does not perturb the structuring or independence of the repetitive units in solution and also that CTDs and W unit have a similar overall structural composition.…”
Section: Results and Discussionsupporting
confidence: 82%
“…The main component of aciniform silk is AcSp1 (aciniform spider silk protein 1, spidroin 1), which is produced and stored in the aciniform gland as a highly soluble protein and can be readily spun into solid fibers. From solution to a solid-state fiber, AcSp1 undergoes a structural transition from globular helical domains connected by intrinsically disordered linkers , to a similar proportion of disorder alongside a mixture of oriented β-sheet and α-helical domains . α-Helix to β-sheet conversion is believed to provide strength to silk fibers. , …”
Section: Introductionmentioning
confidence: 99%
“…From Figure 6 c, we can observe higher R 2 /R 1 values at 25 °C than 50 °C. The average tumbling time (τ c ) values calculated from R 2 /R 1 were 12.657 ns and 5.012 ns at 25 °C and 50 °C, respectively [ 40 , 41 ], indicating that the protein tumbles twice as fast at high temperature as it does at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…From the R 1 and R 2 data, it was confirmed that the residues that experience fast dynamics were more prominent at 50 • C, and the overall motion of the protein was faster at a higher temperature. From Figure 6c, we can observe higher R 2 /R 1 values at 25 • C than 50 • C. The average tumbling time (τ c ) values calculated from R 2 /R 1 were 12.657 ns and 5.012 ns at 25 • C and 50 • C, respectively [40,41], indicating that the protein tumbles twice as fast at high temperature as it does at room temperature.…”
Section: Backbone Dynamics Of Ssossb1-114 At High Temperature and Roo...mentioning
confidence: 91%
See 1 more Smart Citation